Use of road underpasses by terrestrial tetrapods inside a protected area in the southeastern part of the State of São Paulo, Brazil - Alves, Francisco de Assis [UNESP]; Teixeira, Carlos Roberto [UNESP]; Barbosa, Luciano [UNESP]; Júnior, Jairo Alves (FapUNIFESP (SciELO), 2021)
Roads, despite playing a key role in economy, begin or aggravate processes of forest fragmentation and lead to several species losing their natural habitats, acting as filters and barriers that impose challenges to animal locomotion. Wildlife crossings seek to reestablish the connectivity of the landscape. In general, after being installed, these passages need to be evaluated regarding their functioning. In this study, we present the results of monitoring the underpasses on Serra da Macaca Park Road (SP-139), which crosses Carlos Botelho State Park. The underpasses, constituted by bridges and culverts, were constructed after a license obtained to restore this section of the road. Camera traps were installed inside all crossing structures, and systematic samples were obtained through four field expeditions, with sampling efforts of 10 days each, between March 2018 and February 2019. The footprints found around the intersection structures were also considered. A two-sided Student’s t-test was applied to verify differences in richness between the underpasses that have distinct types of margins. Differences in abundance were analyzed through the non-parametric Mann-Whitney test. A Whittaker diagram was generated according to the order of the species, from the most common to the rarest, while their diversity was estimated through Simpson’s Diversity Index (1 – D). The Pearson correlation coefficient was used to study the interaction between diversity and altitude variation. We observed a richness of 16 species of terrestrial tetrapods, without any statistically significant differences between underpasses with dry or flooded margins. Cuniculus paca was the most abundant species, and higher altitudes presented the most diversity. We concluded that the underpasses located inside Permanent Preservation Areas (PPAs) of watercourses are essential to maintain the flow of animals beneath the road.
Uso de pontes e galerias rodoviárias por tetrápodes terrestres em uma área protegida na região sudeste do Estado de São Paulo
Keywords: Connectivity; Mitigation; PPA of watercourses; Wildlife crossing